Leveraging Technologies to Redefine Business: Technology Perspective - Lakshmi, B. Vijaya; Kumar, B. Ravi (American International Journal of Multidisciplinary Scientific Research, 2018)
The disruptors in the financial services industry are rewriting the rules, banks used to perform operations traditionally. The financial services industry known for conservative and resistant to change has been challenged by financial technology (fintech) companies that compete by combining digital technology, social media, and big data analytics to replace traditional models with financial products and services enabled by new technology. The present study is an attempt to portray the Role of Fin Techs, Challenges etc.